IMPROVEMENT OF TH EMETHODOLOGICAL SYSTEM FOR TRAINING COMPUTER TEACHERS BASED ON THE INTEGRATION APPROACH - Kayumova, Nasiba Ashurovna; Suropov, Bakhodir Maidonovich (The journal of contemporary issues in business and government, 2021)
The article examines the integration of pedagogicaland information technologies as an integrative approach to education,the creators of an integration environment,identifying problems in this environment,showing their solutions,integrating pedagogicaland information technologies in computer education ,its pedagogical and psychological aspects and opportunities,pedagogicaland informational.Preparation of informatics teachers for the integration of technologies,the development of requirements for them,the formation of professional competencies,selfdiagnostics,training in the formation and development of their own methodological system,experimental testing of these processes in pedagogical practice and analysis of the results of experiments, conclusionsand recommendations.